ANALISIS PENERAPAN STRATEGI SUMBER DAYA MANUSIA PADA PT SAUNG PINUS SENTOSA - Muchammad Hamdani; Mujito Mujito (Economicus : Jurnal Ekonomi dan Manajemen, 2023)
The purpose of this study is to identify how the management of PT Saung Pinus Sentosa manages human resources, specifically in job analysis, salary distribution, benefits, recruitment, appraisal and labor unions which are then compared with the theories obtained from references. The method used to investigate and identify this is through interviews with management which were held at the PT Saung Pinus Sentosa office. Based on these interviews, it can be concluded that PT Saung Pinus Sentosa has implemented the theory of Human Resource Management in its company, even though some have not been implemented, but overall this company has been running effectively.